SecNav: Secure Broadcast Localization and Time Synchronization in Wireless Networks - Rasmussen, K; Capkun, S; Cagalj, M (ACM Press, 2007)
We propose SecNav, a new protocol for securing wireless navigation systems. This protocol secures localization and time-synchronization in wireless networks by relying on devices' awareness of presence in the power-range (coverage area) of navigation stations. We perform a detailed security analysis of SecNav and we show that, compared to existing secure navigation approaches, it prevents the widest range of attacks on navigation.